FAKTOR RISIKO KEJADIAN TUBERKULOSIS PARU BTA POSITIF DI WILAYAH PUSKESMAS SUNGAI DURIAN KABUPATEN KUBU RAYA TAHUN 2021 - Emi Utami; Ari Udijono; Moh. Arie Wuryanto; Nissa Kusariana (Jurnal Kesehatan Masyarakat (Undip), 2022)
Tuberculosis, hereinafter abbreviated as TB, is an infectious disease caused by Mycobacterium tuberculosis, which can attack the lungs and other organs. lungs) such as the pleura, lymph nodes, bones, and other extra-pulmonary organs.2 TB disease is caused by the bacterium Mycobacterium Tuberculosis, this bacterium is rod-shaped and acid-fast, so it is also known as Acid-Resistant Bacillus (BTA).2 Sources of transmission are patients with TB smear positive, which can transmit to people around him, especially close contacts. When the patient coughs or sneezes, the patient spreads germs into the air in the form of droplet nuclei. One cough can produce about 3000 phlegm sprinkling. A person's transmission power is determined by the number of germs expelled from his lungs. The higher the degree of positivity of the sputum examination results, the more infectious the patient is. The factors that allow a person to be exposed to TB germs are determined by the concentration of splashes in the air and the duration of inhaling the air. This research method is an observational analytical study with a case-control design using a retrospective study approach, namely to analyze the effects of disease or health status at this time and measure the risk factors that influence the incidence of pulmonary TB AFB (+) in the past. The number of samples as many as 90 respondents, with a comparison of cases: control (1:1), conducted by means of interviews and observations. The results of the chi square test showed that there was a relationship between occupancy density (P: 0.027; OR: 3,063), lighting (P: 0.000; OR: 7,429), ventilation area (P: 0.000; OR: 6,329), humidity (P: 0.002; OR). : 4,462), with the incidence of pulmonary TB smear (+). The conclusion is that there is a relationship between environmental risk factors and the incidence of filariasis, so it is necessary to do prevention efforts by reducing risk factors and educating the public about efforts to promote and prevent the transmission of pulmonary TB smear (+).